Subsurface density structure of Taurus‐Littrow Valley using Apollo 17 gravity data. Issue 6 (3rd June 2017) - Urbancic, N.; Ghent, R.; Johnson, C. L.; Stanley, S.; Hatch, D.; Carroll, K. A.; Garry, W. B.; Talwani, M.
Abstract: The Traverse Gravimeter Experiment (TGE) from the Apollo 17 mission was the first and only successful gravity survey on the surface of the Moon, revealing the local gravity field at Taurus‐Littrow Valley (TLV). TLV is hypothesized to be a basalt‐filled graben, oriented radial to Serenitatis basin. We implemented modern 3‐D modeling techniques using recent high‐resolution Lunar Reconnaisance Orbiter topography and image data sets to reinvestigate the subsurface structure of TLV and constrain the volcanic and tectonic history of the region. Updated topography led to significant improvements in the accuracy of free‐air, Bouguer, and terrain corrections. To determine the underlying geometry for TLV, we tested a range of possible thicknesses, dips, and wall positions for the graben fill. We found that the thickness and position previously determined by Talwani et al. (1973) represent our preferred model for the data, but with walls with dips of 30°, rather than 90°. We found large model misfits due to unmodeled 3‐D structure and density anomalies, as well as parameter trade‐offs. We performed a sensitivity analysis to quantify the parameter trade‐offs in an ideal future survey, assuming dominantly 2‐D geological structure. At the TGE survey noise level (2.5 mGal), the fill thickness was constrained to ±150 m, the wall angle to ± 5 ∘ 2 0 ∘ and the wall positions to ±1 km of the preferred model. This information can be used to inform the design of future lunar gravimetry experiments in regions similar to TLV. Key Points: Reanalyzed data from Apollo 17 Traverse Gravimeter Experiment using modern techniques Results are consistent with previous analysis and place new error bounds on the data Investigated noise requirements for future lunar gravimetry experiments